Facebook groups as citizen science tools for plant species monitoring. Issue 10 (17th May 2021) - Marcenò, Corrado; Padullés Cubino, Josep; Chytrý, Milan; Genduso, Emanuele; Salemi, Dario; La Rosa, Alfonso; Gristina, Alessandro Silvestre; Agrillo, Emiliano; Bonari, Gianmaria; Giusso del Galdo, Gianpietro; Ilardi, Vincenzo; Landucci, Flavia; et al.
Abstract: Social networks offer communication channels through which people share huge amounts of primary data that can be used for scientific analyses, including biodiversity research. To understand to what extent data extracted from social networks could complement data collected for scientific purposes, it is necessary to quantify the bias of such data. We analysed which plant traits increased the probability of a wild‐growing plant species to be photographed and posted to a social network based on the data from an unstructured citizen science tool; a Facebook group focused on the vascular flora of Sicily (Italy). Then, we compared botanical data collected by this Facebook group members with data collected by scientists in 6, 366 vegetation plots sampled across Sicily, stored in the EVA database. Our results suggested that data proceeding from the analysed Facebook group were affected by various sampling biases, which differed from the biases inherent to other types of biodiversity data such as those from vegetation plots. Facebook users recorded a higher proportion of red‐listed and alien species than vegetation scientists. Therefore, social networks can provide a valuable complement to the data collected by scientists for research purposes. Synthesis and applications . Despite Facebook does not support geotagging and interface for data access and analysis, it is an invaluable source of biodiversity data that could complement those collected by professional researchers. The main advantage of data from social networks is their high dynamism, as they report large amounts of species occurrences in almost real time. Therefore, citizen science data from a Facebook group where the records are curated by expert volunteers can be used (a) for monitoring population dynamics of threatened and alien species; (b) as a source of additional data on rare species occurrences, particularly for plants that are attractive for amateur botanists, such as orchids; (c) for early warning systems of potential new invasions; and (4) for phenological studies, especially at the beginning of the flowering season. Abstract : Despite Facebook does not support geotagging and interface for data access and analysis, it is an invaluable source of biodiversity data that could complement those collected by professional researchers. The main advantage of data from social networks is their high dynamism, as they report large amounts of species occurrences in almost real time. Therefore, citizen science data from a Facebook group where the records are curated by expert volunteers can be used (a) for monitoring population dynamics of threatened and alien species; (b) as a source of additional data on rare species occurrences, particularly for plants that are attractive for amateur botanists, such as orchids; (c) for early warning systems of potential new invasions; and (d) for phenological studies, especially at the beginning of the flowering season. Sommario: I social network sono canali di comunicazione utilizzati per condividere enormi quantità di dati, che possono essere utilizzati per la ricerca scientifica, anche nel campo della biodiversità. Per sapere quanto i dati ricavati dai social network possono integrare quelli raccolti per scopi scientifici, è necessario individuarne i bias. Utilizzando i dati estratti da un gruppo Facebook specializzato nella flora vascolare siciliana, abbiamo analizzato quali sono i caratteri che aumentano la probabilità che una pianta spontanea venga fotografata e postata su un social network. A tal fine, abbiamo confrontato frequenze e attributi delle specie fotografate dai membri del gruppo Facebook con quelli delle specie registrate nel database EVA, relative a 6.366 rilevamenti vegetazionali della Sicilia. I nostri risultati suggeriscono che i dati provenienti dal gruppo Facebook analizzato sono affetti da bias diversi da quelli relativi a dati floristici raccolti per altri fini, ad esempio, per il rilevamento della vegetazione. I membri del gruppo Facebook hanno intercettato con maggior frequenza specie aliene e specie rare rispetto a quanto rilevato da chi studia la vegetazione, dimostrando che i dati contenuti nei social network offrono un importante complemento a quelli raccolti dagli scienziati per fini di ricerca. Sintesi e applicazioni . Malgrado Facebook non supporti la georeferenziazione dei dati, né una query per l'accesso e l'analisi degli stessi, esso rappresenta una potenziale fonte di dati sulla biodiversità, utili per integrare quelli raccolti da botanici professionisti. Il principale vantaggio dei dati provenienti dai social network è il loro elevato dinamismo, poiché registrano la presenza di una data specie quasi in tempo reale. Pertanto, i dati raccolti da gruppi Facebook moderati da esperti possono risultare utili (1) per monitorare le dinamiche di popolazione di specie minacciate ed esotiche; (2) come informazioni aggiuntive sulla presenza di specie rare, in particolare per quelle che maggiormente attraggono i botanici dilettanti, come le orchidee; (3) per individuare tempestivamente la presenza di nuove esotiche potenzialmente invasive; (4) per studi fenologici, in particolare per monitorare l'inizio della stagione di fioritura delle specie.